Odpowiedzi

  • Użytkownik Zadane
2009-11-24T12:43:44+01:00
załącznik zad 2 a 3 nie wiem napisz wieczorem to ci to zrobię
2009-11-24T12:43:55+01:00
A) 5(x-1)+3=3x-4
5x-5+3=3x-4
2x=-6/2
x=-3
b) x-3/2=6x-3/5
-5x=3/2-3/5
-5x=15/10-6/10
-5x=9/10 /-5
x= -9/50
x=-0,18
c) (x-3)(x+4)-2(3x-2)=(x-4)²
x²+4x-3x-12-6x+4=x²-8x+16
-3x=24/-3
x=-8
  • neli
  • Początkujący
2009-11-24T13:03:52+01:00
Odp: a/(x-1)+3=3x-4
5x-5+3=3x-4
5x-3x=-4+5-3
2x=-7+5
2x=-2/:2
x=-1
b/x-3/2=6x-3/5
x-6x=-3/5+3/2
-5x=-6/10+15/10
-5x=9/10/:-5
x=9/10:-5/1=9/10*-1/5=-9/50
c/(x-3)(x+4)-2(3x-2)=(x-4)²
x²-4x-3x-12-6x+4=x²-8x+16
x²-x²+8x-4x-3x-6x=16+12-4
8x-7x-6x=28-4
8x-13x=24
-5x=24/:-5
x=-24/5
x=-4 4/5 d/(x-6)=4
x=4+6
x=10